2009
DOI: 10.1111/j.1365-2559.2009.03356.x
|View full text |Cite
|
Sign up to set email alerts
|

Serrated polyps of the large intestine: a molecular study comparing sessile serrated adenomas and hyperplastic polyps

Abstract: HPs and SSAs may be related lesions. However, at least right-sided SSAs differ from left-sided SSAs and HPs in the occurrence of MLH1 and p16 methylation, supporting the hypothesis that SSAs could be precursors of serrated adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
32
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 43 publications
6
32
0
2
Order By: Relevance
“…13,14,22,25,26 In previous reports, 18-100% of adenomas and 78% of adenocarcinomas of the colorectum displayed nuclear b-catenin immunoreactivity. 14,22,25 Various investigators have reported that nuclear b-catenin expression was observed in 0-60% of SSA/Ps, 7,9,13,14,22,25,26 43-100% of SSA/Ps with high-grade dysplasia, 9,13,14 and 60% of SSA/Ps with submucosal carcinoma. 13 Nuclear b-catenin labeling indices in our study were significantly lower in the SSA/P series than the adenoma series, suggesting that levels of WNT/b-catenin signaling activation may be different between the serrated neoplasia pathway and the conventional adenoma-carcinoma sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…13,14,22,25,26 In previous reports, 18-100% of adenomas and 78% of adenocarcinomas of the colorectum displayed nuclear b-catenin immunoreactivity. 14,22,25 Various investigators have reported that nuclear b-catenin expression was observed in 0-60% of SSA/Ps, 7,9,13,14,22,25,26 43-100% of SSA/Ps with high-grade dysplasia, 9,13,14 and 60% of SSA/Ps with submucosal carcinoma. 13 Nuclear b-catenin labeling indices in our study were significantly lower in the SSA/P series than the adenoma series, suggesting that levels of WNT/b-catenin signaling activation may be different between the serrated neoplasia pathway and the conventional adenoma-carcinoma sequence.…”
Section: Discussionmentioning
confidence: 99%
“…24 Rare occurrence of BRAF mutations has been documented for conventional adenomas (0-5%), although they are frequent in SSA/Ps (50-90%). 4,[6][7][8][9][10][11][12][13] In contrast, KRAS mutations have shown to be rare in SSA/Ps (0-8%), but more common in conventional tubular adenomas (5-37%). 4,6,10,11,13 In our study, BRAF mutations were frequent (82%), whereas KRAS mutation was not detected in SSA/ Ps, with clearly contrasting results for tubular adenomas (BRAF mutation, 0%, KRAS mutation, 26%).…”
Section: Modern Pathology (2015) 28 146-158mentioning
confidence: 99%
See 1 more Smart Citation
“…28 Because HPs and SSAs are common findings in HPS and have been shown to be difficult to differentiate microscopically, all serrated polyps were included in the criteria. [31][32][33][34] Patients with a known germline APC mutation or a bi-allelic MUTYH mutation were excluded from the study. The study was conducted in accordance with the research code of the institutional medical ethical committee on human experimentation of the Academic Medical Center and in agreement with the Helsinki Declaration of 1975 as revised in 1983.…”
Section: Patientsmentioning
confidence: 99%
“…However, there are few analyses focussing on p16 Ink4a . Up to now it is known that the expression of p16 Ink4a is upregulated in hyperplastic polyps and sessile serrated adenomas 19 and that promoter methylation of CDKN2A can be observed in serrated carcinomas. 20,21 Our work is the first comprehensive analysis of the expression and promoter methylation of CDKN2A in the spectrum of serrated lesions of the colon with BRAF mutation.…”
mentioning
confidence: 99%